Usulan Strategi Endorsement Untuk Meningkatkan kepercayaan Konsumen Terhadap Kualitas Produk (Studi Perusahaan Retail : Nunu Leather) - Anne Fauziyah; Cecep Safa’atul Barkah; Tetty Herawaty; Lina Auliana (Sains: Jurnal Manajemen dan Bisnis, 2021)
The importance of product quality can influence consumer behavior, especially consumer beliefs. Consumer beliefs is very important for the development of a business. This study aims to analyze the level of consumer beliefs in product quality and propose appropriate marketing strategies to increase consumer beliefs in product quality. This research uses mixed research methods with a case study approach. The data used in this study are primary data obtained from interviews with the owner of Nunu Leather and secondary data obtained from textbooks, journals, and internet sites. Methods of data analysis using Internal Based Resources, VRCN, SCA, and TOWS analysis. The results show that consumer beliefs of 85,1% has already reached the target of 82%, but Nunu Leather has a further target of 90%. The author recommends strategy support with a product review program proposal to increase consumer beliefs in the quality of Nunu Leather products by 4,9%.